Antibacterial Effect of Mint Leaf and Basil Leaf Extract addition to Pineapple Hump Extracts Against Streptococcus Mutans Bacteria - Naning Nur Handayatun; David Rudi; Haflin Haflin; Qurati Ayun (Jurnal Kesehatan Gigi, 2023)
The use of herbal ingredients for dentistry is preferable to the use of chemicals. Pineapple is one of the fruits that can be used in dentistry. Pineapple hump is often not consumed even though it still contains many bromelains. This study aimed to see the antibacterial effect of adding mint and basil leaf extract into pineapple hump extract. This type of research is a pure experimental study with a control group design and partly water. This study's experimental group or independent variables were pineapple hump extract, mint leaf extract, and basil leaf extract. The control group was Chlorhexidine and water. The variable is Streptococcus mutans. The extract was made by maceration technique, and the examination of the inhibition of bacteria was carried out using an oxoid blank disc. There was a difference in inhibition against Streptococcus mutans between the experimental and control groups p0.05, but there was no difference between the pineapple hump extract with the addition of min leaf extract and the pineapple weevil extract with the addition of basil leaves. Adding mint and basil leaf extract to pineapple hump extract can increase its antibacterial power against Streptococcus mutans.